2014
DOI: 10.1111/jgh.12551
|View full text |Cite
|
Sign up to set email alerts
|

Decreased density of CD3+ tumor‐infiltrating lymphocytes during gastric cancer progression

Abstract: Background and Aim: Tumor cells escape host immunosurveillance and thus produce an advantageous environment for tumor progression. Recent studies have demonstrated that tumor-infiltrating lymphocytes (TILs) play a principal role in the immune response to tumors. However, little is understood about numerical alterations in CD3+ TILs during tumor progression in patients with gastric cancer. The present study examines the density of CD3+ TILs to elucidate their clinical significance in gastric cancer. Methods:The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…In contrast, TILs represent the host immune response to tumor proliferation and metastasis (2,28). CD8 þ T cells, which are cytotoxic T lymphocytes (CTLs), demonstrate cytotoxic activity toward tumor cells by triggering apoptosis, and are considered to be the frontline defense against cancer (29)(30)(31)(32). Several recent clinical studies have evaluated the role of TILs as prognostic and predictive factors (11), and have shown that CD8 þ TILs are associated with longer disease-free survival (DFS) and overall survival (OS) in colon and ovarian carcinoma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, TILs represent the host immune response to tumor proliferation and metastasis (2,28). CD8 þ T cells, which are cytotoxic T lymphocytes (CTLs), demonstrate cytotoxic activity toward tumor cells by triggering apoptosis, and are considered to be the frontline defense against cancer (29)(30)(31)(32). Several recent clinical studies have evaluated the role of TILs as prognostic and predictive factors (11), and have shown that CD8 þ TILs are associated with longer disease-free survival (DFS) and overall survival (OS) in colon and ovarian carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, forkhead box protein 3-positive (FoxP3 þ ) TILs, which are regulatory T cells (Tregs), are thought to suppress mainly antitumor immunity and immunotherapy, as they effectively suppress the proliferation and activation of CTL (30)(31)(32). It is reported that FoxP3 þ TILs are associated with worse prognosis in breast cancer, gastric cancer, and melanoma (29)(30)(31)(32)(33). Furthermore, in esophageal cancer, it has been reported that a stratification based on PD-L1 expression and CD8 þ TIL status is associated with overall survival (34).…”
Section: Introductionmentioning
confidence: 99%
“…It is required for T‐cell activation. Although CD3 is an established total T‐cell marker, higher numbers of CD3 + TILs have been associated with a favourable prognosis in patients with several malignancies . Cluster of differentiation 5 (CD5) is constitutively expressed on lymphocyte precursors, on mature T cells and on a subset of mature B cells.…”
Section: Introductionmentioning
confidence: 99%
“…The flow diagram for study selection is shown in Figure 1. Table II summarized the characteristics of all included studies [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. The summarizes should represented by summarized incorporated studies were published from 2003 to 2016 and conducted in China (n = 6), Germany (n = 1), Korea (n = 6), Japan (n = 3), America (n = 1), and Italy (n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…Eight papers [15,17,20,24,25,27,29,30] investigated the prognostic value of CD3+ TILs in gastric cancer patients. Seven studies [15,20,24,25,27,29,30] researched the connection of CD3+ TILs in the intratumoral site with OS, with a pooled HR of 0.610 for TILs-high cases (95% CI: 0.526-0.708, p < 0.001), without any heterogeneity (Figure 2 B). Only one study [17] reported the CD3+ TILs in tumor stroma (TS) and tumor parenchyma (TP), and the results showed that HRs for DFS were 0.86 (95% CI: 0.33-2.23, p = 0.76) and 0.76 (95% CI: 0.29-1.98, p = 0.58) respectively.…”
Section: Cd3+ T Lymphocytesmentioning
confidence: 99%